Human brain activity and functional connectivity as memories age from one hour to one month. Issue 3 (2nd October 2022) - Tallman, Catherine W.; Clark, Robert E.; Smith, Christine N.
ABSTRACT: Theories of memory consolidation suggest the role of brain regions and connectivity between brain regions change as memories age. Human lesion studies indicate memories become hippocampus-independent over years, whereas animal studies suggest this process occurs across relatively short intervals, from days to weeks. Human neuroimaging studies suggest that changes in hippocampal and cortical activity and connectivity can be detected over these short intervals, but many of these studies examined only two time periods. We examined memory and fMRI activity for photos of indoor and outdoor scenes across four time periods to examine these neural changes more carefully. Participants (N = 21) studied scenes 1 hour, 1 day, 1 week, or 1 month before scanning. During scanning, participants viewed scenes, made old/new recognition memory judgments, and gave confidence ratings. Memory accuracy, confidence ratings, and response times changed with memory age. Brain activity in a widespread cortical network either increased or decreased with memory age, whereas hippocampal activity was not related to memory age. These findings were almost identical when effects of behavioral changes across time periods were minimized. Functional connectivity of the ventromedial prefrontal cortex with the posterior parietal cortex increased with memory age. By contrast, functional connectivity of the hippocampus with the parahippocampal cortex and fusiform gyrus decreased with memory age. In sum, we detected changes in cortical activity and changes in hippocampal and cortical connectivity with memory age across short intervals. These findings provide support for the predictions of systems consolidation and suggest that these changes begin soon after memories are formed.